Nano-structural analysis of fish collagen extracts for new process development - Jaswir, Irwandi; Monsur, Hammed Ademola; Mohd. Salleh, Hamzah (2011)
Nano and micro imaging were used to evaluate effects of pretreatment solution on gelatin. Four types of pre-treatment solution were used during fish gelatin extraction in this study. They were acetic acid (A), acetic acid-NaCl (SA), acetic acid-NaOH (BA) and acetic acid-NaOH-NaCl (SBA). Different pattern was observed for gelatins pretreated differently. Results showed that each pretreatment gave different nano imaging patterns; A (fibril), SA (zig-zag cracks), BA (straight rods) and SBA (cross-linked rods). Cross-linked rods observed in SBA denote adequate removal of non-collagen content of the fish skin and increase its surface area. SBA is suggested as the best pretreatment for perch fish gelatin. Result of viscosity was also highest for sample SBA (0.02450.0001 pas), while viscosity for others are 0.01550.0002 pas, 0.01230.0001 pas, and 0.00250.0001 pas for samples BA, SA and A, respectively. SDS-PAGE analysis showed presence of α and β in sample SBA and BA.